Mutual Administrative Assistance in Tax Matters - Šumić, Aleksandra (Glasnik Advokatske komore Vojvodine, 2022)
The subject of the analysis is interstate administrative cooperation in tax matters with the aim of faster and more efficient cooperation in terms of exchange of documents, collection of tax claims, submission of documents and unified scope of rights of taxpayers in the signatory states in terms of the Convention on Mutual Administrative Assistance in Tax Matters. The focus of the article is the elaboration of provisions, the standard of data exchange on request and to consider the framework of automatic data exchange in the field of tax interstate cooperation in the future, which is already implemented in many developed countries in national tax legislation.
Keywords: Tax administration; tax evasion; tax matters; cooperation; Convention